METODE RESITASI PADA PEMBELAJARAN IPS DI SMPN.1 SIBERUT UTARA - Pasti, Pasti; Husnita, Liza; Nazmi, Ranti (Pendidikan Sejarah, 2014)
This study pupouse to describeÂ  the increase studentâs motivation in learning Social Sciences (IPS) by using the method of recitation in the classroom of VIII / AÂ  of Junior High School 1 North Siberut. Recitation is giving the task to students. In this case the author gives the task to make a summary and conclusions of matter. Types of Â this research is an action research, then carried out on each cycle of the planning procedure, action, observation and reflection. This research / study was done in two cycles,Â  each cycleÂ  implemented of Â two meetings. The object of research/ study Â is class VII/A of Junior High School 1 North Siberut on 2013/2014Â  in the second semester. The data collected is related to the level of student motivation. Taken from the observation sheet by using a checklist list and the percentage formula. The research showed that by using the method of recitation in learning of Social Sciences ( IPS) especially oinÂ  history subjects can increase students motivation.